Changes in dissolved organic matter composition and dynamics in a subtropical mangrove river driven by rainfall. (31st July 2019) - Kida, Morimaru; Tanabe, Mai; Tomotsune, Mitsutoshi; Yoshitake, Shinpei; Kinjo, Kazutoshi; Ohtsuka, Toshiyuki; Fujitake, Nobuhide
Abstract: Dissolved organic matter (DOM) plays an important role in sustaining ecosystem services of mangrove forests through well-described biogeochemical and ecological functions. This study was conducted in the Fukido River (Ishigaki Island, Japan) to better understand the seasonal and episodic changes in DOM concentration and composition in a subtropical mangrove system. Water samples were collected seasonally along a headwater–mangrove–sea transect on 10 occasions from September 2014 through June 2016. DOM was fractionated based on hydrophobicity into two fractions (hydrophobic and hydrophilic) and also analyzed by excitation-emission matrix spectroscopy combined with parallel factor analysis (PARAFAC). Although seasonal changes in DOM concentration and composition were not observed, both hydrophobic and hydrophilic DOM concentrations and levels of the identified three PARAFAC components clearly increased during a typhoon event. It is suggested that episodic increases in freshwater input due to a typhoon caused enhanced leaching of DOM from mangrove litter and dissolution of mangrove soil organic matter (SOM), which was otherwise retained in the mangrove soil by salinity-induced aggregation. The aggregation–dissolution properties of SOM are crucial in determining the magnitude of DOM outwelling and possibly SOM accumulation rate by enhancing advective DOM exchanges. Future studies are needed to evaluate the size of the carbon pool and outwelling of DOM after classifying mangrove forests based on the hydrological regime that influences biogeochemical conditions in the forests. Regional Index Terms: Japan, Okinawa, Ishigaki, Fukido. Highlights: Hydrology had a great impact on mangrove river DOM concentration and composition. Episodic increases in freshwater input increased mangrove-derived DOM. Dissolution of SOM may be important in determining magnitude of DOM outwelling. Episodic freshwater input is a key for better understanding mangrove elemental cycles.